OPTIMALISASI PEMASARAN PRODUK LOKAL GUNA MENINGKATKAN KUALITAS UMKM DI DESA PERSIAPAN PUNIKAN KECAMATAN LINGSAR, KABUPATEN LOMBOK BARAT - Saputra, Wahyudi Maulida; Sa'adah, Denda; Sumiyati, Sumiyati; Kausari, Lamya; Utari, Sagita (Universitas Mataram, 2023)
Batu Mekar is a village located in the Lingsar District, West Lombok Regency. Batu Mekar Village is a village with great potential, especially in the tourism, agriculture and plantation sectors. Batu Mekar Village has great potential in the plantation sector, the abundant yields of gardens are the leading commodity of the village, but all of them seem paralyzed and are having difficulty getting back up due to the impact of the earthquake and the covid 19 pandemic. This is due to a lack of public awareness to restore their economic conditions by utilizing the abundant plantation products to be processed to become economically valuable and have high competitiveness, making people accustomed to selling their plantation products directly or raw to collectors to be sold and sent outside the area. The hamlets that have great potential in the plantation sector are in the North Punikan and South Punikan hamlets in the form of bananas. However, these banana trees have not been used commercially because of the limited knowledge and skills possessed by the community in processing bananas into products of high economic value. Therefore, it is necessary to carry out empowerment activities related to this problem, to revive economic activities which had stopped due to the 2019 covid disaster. This empowerment activity is a series of Unram Integrated Community Service activities on the theme of Processed Products for the January 2023 period. The program targets are mothers and fathers in two the hamlet. The series of empowerment program activities consists of: marketing workshops, training on processing palm sugar banana chips, packaging, product licensing, product processing assistance, and market surveys. The result of this program is that the women's group in Batu Mekar is able to process bananas into products with high economic value, namely palm sugar banana chips which are expected to become products that can be competitive in the market so that they can increase people's income.